The Effectiveness of Mobile Assisted Language Learning (MALL) on ESL Listening Skill (Universitas Islam Negeri Sunan Ampel Surabaya, 2020)
Using mobile technology in English learning and teaching has been on the rise all over the world over the past few decades and hence, has received considerable attention and importance from academics in recent years. As a result, several experimental studies have been carried out about the use and effectiveness of mobile phones in the teaching/learning process. However, there have been only a few studies on mobile-assisted listening comprehension. This study aims to explore whether Mobile Assisted Language Learning (MALL) is effective in teaching/learning listening skills to the students of university-level English language programs and could better enhance students’ listening ability. It also endeavors to assess why some MALL strategies/techniques are more effective than others. This study uses a qualitative research method. It exclusively uses the relevant secondary materials available on the broader topic- the use and efficacy of mobile phones in teaching/learning listening skills. The results indicated that the MALL is meaningfully efficacious in teaching/learning ESL/EFL listening skills. Therefore, using appropriate strategies could positively contribute to bringing about better learning. Besides outlining a brief overview of MALL, the study also recommends some practical and useful stratagems that ESL/EFL educators can use while designing MALL listening tasks/activities.